1986
DOI: 10.1143/jjap.25.l789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Substrate Offset Angle on the Growth of GaAs on Si Substrate

Abstract: In the growth of GaAs on Si, the effects of the offset angle of the substrate and its direction on the epitaxial layer were studied using spherical Si substrates. The growth was carried out by a low pressure MOCVD system. On the grown layer, milky lines were observed along the [010] and the [001] axis of the substrate. Except for the narrow regions along these milky lines, the grown layer showed a mirror-like surface with a single domain structure. The surface morphology and the etch pit density in the single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Therefore, the total number of ways that the terrace atoms can be distributed within a given sequence is 2) [ (N .. , -n A -n,,) (1) can be interpreted as the contribution of the terrace atoms interspersed among the steps.…”
Section: B Elimination Of Non-1r-bonded Stepsmentioning
confidence: 99%
“…Therefore, the total number of ways that the terrace atoms can be distributed within a given sequence is 2) [ (N .. , -n A -n,,) (1) can be interpreted as the contribution of the terrace atoms interspersed among the steps.…”
Section: B Elimination Of Non-1r-bonded Stepsmentioning
confidence: 99%
“…The domains themselves are called antiphase domains (APD) [20,21]. Such APD's were observed in several systems like GaAs/Si [22], Gap /Si [23], GaAsIGe [24].…”
Section: Polar-non Polar Epitaxy and Antiphase Disordermentioning
confidence: 99%
“…Moreover, Akiyarna el a1. [34,22] have performed GaAs growth on lens-shaped Si substrate, which presents a continuum of both directions and magnitude of tilt, and they observed that APB's occur only in a narrow range of tilt direction near an exact [Wl] and [0101 tilt APBs as pointed out by Kroemer [35] might not occur for (21 1) or (1 10) crystallographic orientations. On (211) or (1 10) surfaces the atomic sites of the two sublattices have a different number of back bonds to the Si or Ge substrate (Fig.2).…”
Section: Polar-non Polar Epitaxy and Antiphase Disordermentioning
confidence: 99%
“…В 1986 году сразу несколькими исследовательскими группами было продемонстрировано [6,7], что однодоменные пленки GaAs могут быть выращены на поверхности Si(001) методом эпитаксии (МЛЭ либо МОГФЭ). Необходимым условием для этого является использование подложек, отклоненных на 2−6 угловых градуса к плоскости (111).…”
Section: Introductionunclassified